Septuple XBi2Te4 (X=Ge, Sn, Pb) intercalated MnBi2Te4 for realizing interlayer ferromagnetism and quantum anomalous hall effect - Ruixia Yang; Xiaoxiao Man; Jiahui Peng; Jingjing Zhang; Fei Wang; Fang Wang; Huisheng Zhang; Xiaohong Xu (npj Quantum Materials)
Abstract Realizing the quantum anomalous Hall effect (QAHE) at high temperatures remains a significant challenge in condensed matter physics. MnBi2Te4, an intrinsic magnetic topological insulator, presents a promising platform for QAHE. However, its inherent interlayer antiferromagnetic coupling hinders practical realization at high temperatures. In this study, we propose a novel approach to achieve interlayer ferromagnetic (FM) coupling in MBT bilayer by intercalating the septuple-layer of topological insulators XBi2Te4 (X=Ge, Sn, Pb). Using first-principles calculations, we demonstrate that the p z orbital of the X atom mediates interactions between interlayer Mn atoms, enabling FM coupling. Monte Carlo simulations predict a magnetic transition temperature of 38 K for the MnBi2Te4/PbBi2Te4/MnBi2Te4 heterostructure. Our band structure and topological analyses confirm the preservation of QAHE in all MnBi2Te4/XBi2Te4/MnBi2Te4 heterostructures, while the MnBi2Te4/PbBi2Te4/MnBi2Te4 heterostructure exhibits a topological band gap of 72 meV, significantly exceeding that of the pure MnBi2Te4 bilayer. Furthermore, a continuum model is developed to elucidate the underlying mechanism of the nontrivial topological states. Our work provides a practical pathway to achieving interlayer FM coupling in MnBi2Te4 bilayers, paving the way for high-temperature QAHE and advancing the development of magnetic topological insulators for quantum and spintronic applications.